Karakteristik Sensoris dan Organoleptik Choux Pastry: Studi Komparatif Penggunaan Telur Ayam dan Substitusi 25% Telur Bebek - Ragil Fatmawati; Sri Yulianto Fajar Pradapa (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
Choux pastry relies heavily on eggs to form its cavity structure and sensory characteristics. The use of duck eggs can improve physical quality due to their higher protein and fat content compared to chicken eggs. This study aims to analyze the differences in organoleptic quality between choux pastry with 100% chicken eggs and 25% duck egg substitution. The experimental quantitative study involved 50 panelists using a hedonic scale questionnaire and analyzed descriptively. The results showed that 25% duck egg substitution significantly improved texture firmness and provided a more savory taste. However, in terms of aroma, the sample with duck egg substitution scored lower due to a sharper fishy aroma. Although 25% duck egg substitution effectively improved the physical structure, it is recommended to add aromatic ingredients to reduce the distinctive duck egg aroma. These findings provide insights into the development of choux pastry with duck egg substitution to improve physical quality without sacrificing desired organoleptic characteristics.